الحوافز وعلاقتها بأداء العاملين - قويدري، صالح, بوتة، خالد (جامعة الوادي university of Eloued, 2020)
الملخص: من خلال دراستنا سعينا إلى محاولة معرفة علاقة الحوافز بأداء العاملين، في مؤسسة منقر لإنتاج الفرينة والنخالة ببلدية حساني عبد الكريم ولاية الوادي، وتبلورت فكرة البحث من هذا المنطلق، لذلك التجأنا إلى القيام بدراسة ميدانية على عينة من العمال المهنيين في هذه المؤسسة، وقد اعتمدنا في هذه الدراسة على المنهج الوصفي لملائمته طبيعة الموضوع واعتمدنا على أدوات جمع البيانات، المتمثلة في الملاحظة والمقابلة والاستبيان لجمع المعلومات، وكنا بصدد توزيعه على عينة من مجتمع البحث تتكون من 80 مفرد ( عاملا)، ثم تحليل البيانات الواردة في الاستبيان عن طريق استخدام الحزمة الإحصائية للعلوم الاجتماعية (SPSS ) بالاعتماد على معامل الارتباط بيرسون والنسب المئوية للإجابة على التساؤلات المطروحة في الإشكالية بقبول فرضيات الدراسة أو لا وهذا ما يؤدي بنا إلى معرفة العلاقة بين الحوافز وأداء العمال المهنيين لهذه الشركة. Résumé :فرنسية أو إنجليزية Through our study, we sought to try to find out the relationship of incentives to the performance of workers, at the Mnqer Foundation for the production of ferna and bran in the municipality of Hassani Abdul Karim, the state of El-Wadi. This study is based on the descriptive approach for its suitability to the nature of the topic and we have relied on data collection tools, represented in observation, interview and questionnaire to collect information, and we were about to distribute it to a sample of the research community consisting of 80 individuals (workers), then analyze the data contained in the questionnaire by using the Statistical Package for Science (SPSS) based on the correlation coefficient of Pearson and the percentages to answer the questions raised in the problem by accepting the study hypotheses or not, and this leads us to know the relationship between incentives and the performance of the professional workers of this company
دراسة ميدانية على عينة من العمال المهنيين لشركة منقر للفرينة والنخالة بحساني عبد الكريم
مذكرة ماستر في علم الإجتماع تخصص تنظيم وعمل
Keywords: الحوافز، الأداء الوظيفي; Incitations, performance au travail; Incentives, job performance